Exploring medical and veterinary student perceptions and communication preferences related to antimicrobial resistance in Ontario, Canada using qualitative methods - Courtney A. Primeau; Jennifer E. McWhirter; Carolee Carson; Scott A. McEwen; E. Jane Parmley (BMC Public Health, 2023)
Abstract Background Antimicrobial resistance (AMR) threatens our ability to treat and prevent infectious diseases worldwide. A significant driver of AMR is antimicrobial use (AMU) in human and veterinary medicine. Therefore, education and awareness of AMR among antimicrobial prescribers is critical. Human and animal health professionals play important roles in the AMR issue, both as contributors to the emergence of AMR, and as potential developers and implementers of effective solutions. Studies have shown that engaging stakeholders prior to developing communication materials can increase relevance, awareness, and dissemination of research findings and communication materials. As future antimicrobial prescribers, medical and veterinary students’ perspectives on AMR, as well as their preferences for future communication materials, are important. The first objective of this study was to explore medical and veterinary student perceptions and understanding of factors associated with emergence and spread of AMR. The second objective was to identify key messages, knowledge translation and transfer (KTT) methods, and dissemination strategies for communication of AMR information to these groups. Methods Beginning in November 2018, focus groups were conducted with medical and veterinary students in Ontario, Canada. A semi-structured format, using standardized open-ended questions and follow-up probing questions was followed. Thematic analysis was used to identify and analyze patterns within the data. Results Analyses showed that students believed AMR to be an important global issue and identified AMU in food-producing animals and human medicine as the main drivers of AMR. Students also highlighted the need to address society’s reliance on antimicrobials and the importance of collaboration between different sectors to effectively reduce the emergence and transmission of AMR. When assessing different communication materials, students felt that although infographics provide easily digestible information, other KTT materials such as fact sheets are better at providing more information without overwhelming the target audiences (e.g., professional or general public). Conclusion Overall, the study participants felt that AMR is an important issue and emphasized the need to develop different KTT tools for different audiences. This research will help inform the development of future communication materials, and support development of AMR-KTT tools tailored to the needs of different student and professional groups.